TINJAUAN PERHITUNGAN STRUKTUR ATAS GEDUNG PENDIDIKAN TERPADU IAIN AMBON METODE KEKUATAN BATAS - Fariz Vitran Akbar Maruapey; Pieter Lourens Frans; Maslan Abdin; Apri Adam Matitaputty (JURNAL SIMETRIK, 2026)
In Construction Project Management studies, it is essential to analyze and assess the stability and strength of building structures to determine their ability to resist applied loads. In the construction project of the Integrated Educational Building of IAIN Ambon, several structural elements were found not to meet the applicable standards. Therefore, the objective of this study is to design and redesign the dimensions and reinforcement system of the superstructure of the Integrated Educational Building of IAIN Ambon in accordance with the standards. The analysis was conducted using the Limit Strength Method in combination with SAP2000 v.25 to evaluate the safety and serviceability of the structure. The results of the study show that the dimensions of beams and columns meet the requirements of SNI 2847:2019, with dimensions of Beam B1: 750×350 mm, Beam B2: 650×350 mm, and Beam B3: 500×300 mm. Meanwhile, the slab with a thickness of 130 mm was deemed inadequate and replaced with a thickness of 200 mm. Based on the analysis results, the designed reinforcement system satisfies both strength and geometric requirements, ensuring safety and compliance with SNI 2847:2019. Keywords: Superstructure, Limit Strength Method, SAP2000, Safety, Design.